Tragedy, Memory, and Suffering : How Indonesian Readers on Goodreads Interpret Yu Hua’s Cries in the Drizzle - Elizabeth Irene Hartanto (Journal of Chinese Language and Culture Studies, 2026)
This study investigates how Indonesian readers interpret tragedy, memory, and suffering in Yu Hua's novel Cries in the Drizzle (Indonesian translation: Tangis di Rinai Gerimis). While Yu Hua is widely read in Indonesia, no prior research has specifically examined Indonesian readers' spontaneous reception of this novel. The study employs a qualitative reader-response approach combined with thematic analysis. Data are collected from 16 self-identified Indonesian reader reviews on the Goodreads platform, selected through purposive sampling based on self-disclosed location or identity. Reviews are analyzed using Braun and Clarke's (2006) six-phase thematic coding framework to identify recurring interpretive themes. Three major findings emerge. First, Indonesian readers strongly connect the novel's depiction of family dysfunction and childhood trauma to their own cultural understanding of suffering, often expressing emotional catharsis through words like "cried," "heartbroken," and "sad." Second, readers demonstrate cultural bridging, interpreting the novel's tragedy through both Chinese cultural logic (filial piety, familial duty) and Indonesian local contexts. Third, readers express mixed evaluations, appreciating Yu Hua's literary craftsmanship while critiquing the slow pacing and, in some cases, the Indonesian translation quality. This study concludes that Indonesian readers receive Cries in the Drizzle not merely as a foreign literary work but as a text that resonates with universal human experiences of family, memory, and loss. The findings contribute to the limited body of research on the reception of contemporary Chinese literature in Southeast Asia and demonstrate the value of spontaneous online reviews as data for cross-cultural reader-response studies.